Characterization of the wind with the Weibull function for a high Andean zone, Laraqueri - Peru - Yancachajlla Tito, Ubaldo (2022)
It is important to study the availability of renewable energy and in particular wind power for its evaluation. Therefore, this article analyzes the wind energy potential of a site located in southern Peru (Laraqueri), using wind data from 2020 at a height of 10 meters above ground level. Two numerical methods were used to estimate the parameters of the Weibull distribution function and the power density was calculated for each month. The degree of error of the Weibull function was also calculated with the observed data. It is concluded that the proposed location is appropriate for the generation of low power wind power and the proposed methodology can be used in other places.